Studi Penentuan Kawasan Terpilih Pusat Pengembang Desa Pertumbuhan di Kecamatan Obi Utara Kabupaten Halmahera Selatan - Rimba Arief; Allun Abdul; Emil Salim Rasyidi; Rudi Latief (Journal of Urban Planning Studies, 2021)
Abstrak Alun Abdul, 2019 "Study of Determining Selected Areas for Development Village Development Centers in North Obi District, Halmahera Sealataan Regency" . This study aims to determine the area selected for the development center of a village growth center in North Obi District, South Halmahera Regency. This study will analyze two things, namely: (1) identifying the potential of the village and the availability of facilities and infrastructure for each village in North Obi District, (2) determining the appropriate village to be developed as a growth center village in North Obi District. Based on the analysis of the village potential and the availability of facilities and infrastructure, it can be concluded that the existing facilities and infrastructure in North Obi District are generally sufficient. as the Village Growth Center (DPP). among others, are as follows: market facilities, lighting facilities, communication facilities, community institutions, service facilities and accessibility. Pasir Putih Village functions as a driving force for the economy of North Obi District, South Halmahera Regency, because all distribution of goods originating from hinterland villages will be marketed to other areas such as, South Obi District and, Obi District through West Madapolo Village. Keywords : Selected Area Development Village Development Center